2020
DOI: 10.3171/2020.2.spine191517
|View full text |Cite
|
Sign up to set email alerts
|

C2 medial pedicle screw: a novel “in-out-in” technique as an alternative option for posterior C2 fixation in cases with a narrow C2 isthmus

Abstract: OBJECTIVEThe authors describe a novel “in-out-in” technique as an alternative option for posterior C2 screw fixation in cases that involve narrow C2 isthmus. Here, they report the preliminary radiological and clinical outcomes in 12 patients who had a minimum 12-month follow-up period.METHODSTwelve patients with basilar invagination and atlantoaxial dislocation underwent atlantoaxial reduction and fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Pedicle screws insertion is the commonly used technique for C2 fixation. Pedicle screws are combined with C1 lateral mass screws to perform Goel-Harms technique, which is a widely used fixation technique in clinical practice [ 3 , 11 ]. The C2 pedicle screw can directly fix the isthmus and pedicle as a result of its long implant depth, good pull-out strength, and biomechanical stability [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pedicle screws insertion is the commonly used technique for C2 fixation. Pedicle screws are combined with C1 lateral mass screws to perform Goel-Harms technique, which is a widely used fixation technique in clinical practice [ 3 , 11 ]. The C2 pedicle screw can directly fix the isthmus and pedicle as a result of its long implant depth, good pull-out strength, and biomechanical stability [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al and Lee et al have reported the medial “in–out-in” technique, which prevents VA injury by opening a window through the wall of the spinal canal to achieve multi-cortical tri-column fixation. Although no spinal cord injury has been reported, the screw entering the spinal canal poses a certain threat to the spinal cord [ 3 , 13 ]. Additionally, Goel performed the VA transposition technique, using two smaller screws for fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with the findings of the present study, which show that the cervical vertebrae in children between the ages of eight and 14 years were still growing. The C2 “in‐out‐of‐in” technique has been available for years (Du et al, 2020). For children with narrow pedicles and high vertebral artery spans, the screw length should be increased and the width decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Routt et al suggested iliosacral screw insertion into the sacral isthmus region required avoidance of IOI to reduce the risk of damage to the adjacent neurovascular structures 12 . Du et al recommended the C2 pedicle screw IOI to provide multicortical 3-column rigid xation in the patients with basilar invagination and atlantoaxial dislocation 13 . Ramesh et al proposed anterior column lag screw IOI in the xation of acetabular fractures to provide rigid stability and minimize the surgical duration, radiation exposure, and intra-operative complications 14 .…”
Section: Discussionmentioning
confidence: 99%